Ion energy distribution and basic characteristics of plasma flows of nonself-sustained arc discharge - Borisenko, A.G.; Podzirei, Yu.S. (Вопросы атомной науки и техники, 2015)
Experimental results on study of the nonself-sustained arc discharge basic characteristics at currents up to 35 A are presented. The ion energy distributions and dynamics of the directed motion average energy of plasma flow ions are studied. Floating potentials in the plasma flows are measured. Ionization coefficients of the generated plasma flows and their dependence on the discharge current are studied. It is shown that at the discharge currents equal 20…30 A the vacuum arc discharge in anode material vapors can effectively create dropless and highly ionized plasma flows of different metals and provides films deposition rates, which are comparable to possibilities of the cathode vacuum arc discharge.